ACT-FASTER, a Prospective Cohort Study Exploring Treatment Patterns with Fulvestrant and Exemestane in Postmenopausal Patients with Advanced Hormone Receptor-Positive Breast Cancer under Real-Life Conditions in Germany - Maass, Nicolai (Breast Care (Basel), 2019)
BACKGROUND: Endocrine therapy is recommended for the treatment of postmenopausal women with hormone receptor-positive (HR+) advanced breast cancer (ABC). METHODS: ACT-FASTER was a German prospective non-interventional cohort study in postmenopausal women with HR+ ABC receiving fulvestrant 500 mg as first line (1 L), second line (2 L) or third line (3 L), or exemestane (any line) in the real-world palliative setting. Primary study objectives included the effectiveness of fulvestrant according to line of palliative treatment measured by time to progression (TTP), and real-life data on the epidemiology and management of these patients. RESULTS: Of 498 evaluable patients (mean age 67.5 years), 99% were estrogen receptor-positive. On study, 86.7% of patients received fulvestrant 500 mg and 13.3% exemestane. Median TTP was 9.7 months in patients receiving fulvestrant 1 L; 6.8 months for 2 L; and 6.7 months for 3 L. The comparison between fulvestrant 1 L palliative treatment and 2 L or 3 L showed that early initiation of treatment prolonged TTP (hazard ratio 1.26; 95% confidence interval 1.08-1.48). Treatments were well tolerated. CONCLUSION: Fulvestrant 500 mg was administered successfully to patients under daily practice conditions, and both medications were well tolerated. TTP was longest in patients treated with fulvestrant 500 mg 1 L compared with 2 L and 3 L in the palliative care setting.